1995
DOI: 10.1006/viro.1995.1049
|View full text |Cite
|
Sign up to set email alerts
|

Human and Simian Adenoviruses: Phylogenetic Inferences from Analysis of VA RNA Genes

Abstract: Adenovirus VA RNA genes have primary sequence constraints due to internal promoter regions and a high degree of secondary structure in the RNA product. To determine the relationships between human and simian adenoviruses, the VA RNA genes of several primate adenoviruses were characterized and compared to those sequences already published. Human adenoviruses of subgenera A, B:2, and F have only one VA RNA gene, whereas human adenoviruses of subgenera B:1, C, D, and E have two. The genomes of 12 monkey adenoviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 0 publications
9
51
0
3
Order By: Relevance
“…In addition, a close genetic relationship has been reported to exist between the HAdVs and SAdVs (17,25). When we selected SAdV-21 for comparison, we found that HAdV-11 QS also exhibited a high degree of amino acid sequence homology (average, Ͼ90%) with SAdV-21, except in the fiber region ( Table 2), which enabled differentiation between the AdV species and interaction with the receptor on the target cells.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, a close genetic relationship has been reported to exist between the HAdVs and SAdVs (17,25). When we selected SAdV-21 for comparison, we found that HAdV-11 QS also exhibited a high degree of amino acid sequence homology (average, Ͼ90%) with SAdV-21, except in the fiber region ( Table 2), which enabled differentiation between the AdV species and interaction with the receptor on the target cells.…”
Section: Discussionmentioning
confidence: 82%
“…Numbers of AdVs found in each host species are given in parentheses: numbers of published AdVs are given before the slash, in black, and numbers of novel AdVs from this study are given behind the slash, in blue. 55), and most studies on NHP AdVs involve captive animals from zoos and animal facilities (3,4,6,10,24,30,31,33,34,36,40,45,46,56,61). Therefore, our study on wild primates is of importance because it provides insight into natural AdV diversity and evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The consensus promoter sequences (A and B boxes) for pol III recognition have previously been characterized for various genes (Fowlkes & Shenk, 1980) and for human and simian adenoviruses (Ma & Mathews, 1993 ;Kidd et al, 1995). For CELO virus VA RNA, only minimal similarity is shared in the region of the B box (Larsson et al, 1986 ;Ma & Mathews, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For CELO virus VA RNA, only minimal similarity is shared in the region of the B box (Larsson et al, 1986 ;Ma & Mathews, 1993). The element GGTTC is highly conserved in the B box of many pol III-transcribed genes, but GGaTC is allowed in some cases (Fowlkes & Shenk, 1980 ;Bandea et al, 1992 ;Ma & Mathews, 1993 ;Kidd et al, 1995). Within the left-hand OAV FBD A. Venktesh and others A. Venktesh and others ORFs which show homology within and across genomes are indicated by the same symbol.…”
Section: Discussionmentioning
confidence: 99%